Rendering Life Molecular : Models, Modelers, and Excitable Matter - Myers, Natasha, 1974- (Book collections on Project MUSE., 2015)
Natasha Myers shows in this ethnography how scientists who build three-dimensional models of proteins use their senses and bodies to create, represent, and evaluate otherwise imperceptible molecules. These modelers often consider matter to be made up of living, moving, and sometimes breathing entities, and Myers' study of them rethinks the objectivity of science.